Synthesis of Ag-La0.8Sr0.2MnO3 (LSM-Ag) Composite Powder and Its Application in Magnesium Air Battery - Xiaohan Wu; Hui Liu; Jiaxi Zhang; Juemin Song; Jiefeng Huang; Wanli Xu; Yang Yan; Kun Yu (Metals, 2021)
La0.8Sr0.2MnO3 (LSM) catalyst is prepared via a sol-gel method and modified via a typical silver mirror reaction. Silver ammonia solution is reduced in a polyvinylpyrrolidone (PVP)-containing solution to obtain silver nanoparticles and sodium dodecyl sulfate (SDS) is added as a surfactant. The microstructure and morphology of the LSM-Ag composite powder are characterized. According to the results, the Ag particles precipitate on the LSM surface in elemental form and the grain size is about one hundred nanometers. The analysis of electrocatalytic performance of LSM-Ag cathodes with different amounts of silver loading reveals that the number of electrons transferred during the oxygen reduction reaction (ORR) of the cathode with an Ag content of 14% by weight reached 3.9, which is very close to that of commercial Pt/C catalysts. Similarly, the maximum power density of the air battery made of LSM-14%Ag is 73 mW/cm2, which exceeds that of 63 mW/cm2, found for the LSM battery. Finally, increasing the amount of silver loading allows one to improve the electrochemical performance of LSM catalysts. The best effect is achieved when the Ag loading exceeds 14%.